2021
DOI: 10.3390/healthcare9060663
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences with the Transition to Telephone Counseling during the COVID-19 Pandemic

Abstract: Background: To identify and document the treatment experiences among patients with opioid use disorder (OUD) in the context of the rapid move from in-person to telephone counseling due to the COVID-19 pandemic. Methods: Participants (n = 237) completed a survey with open-ended questions that included the following domains: (1) satisfaction with telephone counseling, (2) perceived convenience, (3) changes to the therapeutic relationship, (4) perceived impact on substance use recovery, and (5) general feedback. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…To our knowledge, this study is among a very few to report direct patient experience with policy changes in MOUD access during COVID. A telehealth satisfaction survey was conducted in one Rhode Island provider setting [ 35 ], a survey study of North Carolina patients in three methadone clinics was reported [ 36 ], and a very small, non-peer reviewed study in one San Francisco methadone clinic with 10 providers and 20 patients reported views about methadone take-home dosing [ 37 ]. The North Carolina study found that take-home doses increased from pre-COVID periods to the time of the study (summer 2020) from 56–82% to 78–100%, though notably, the clinic-level percent of patients receiving a week or longer (>6 days) ranged from 11–56%.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is among a very few to report direct patient experience with policy changes in MOUD access during COVID. A telehealth satisfaction survey was conducted in one Rhode Island provider setting [ 35 ], a survey study of North Carolina patients in three methadone clinics was reported [ 36 ], and a very small, non-peer reviewed study in one San Francisco methadone clinic with 10 providers and 20 patients reported views about methadone take-home dosing [ 37 ]. The North Carolina study found that take-home doses increased from pre-COVID periods to the time of the study (summer 2020) from 56–82% to 78–100%, though notably, the clinic-level percent of patients receiving a week or longer (>6 days) ranged from 11–56%.…”
Section: Discussionmentioning
confidence: 99%
“…Given the range of COVID-related SUD policy changes that were implemented, understanding the experiences of people involved with those changes will be critical to discussions about any permanent policy changes. To date, few studies have described provider or patient perspectives regarding the impacts of COVID-19 on OUD treatment 25-29 . The present study expands prior work in other states by adding findings from within a sample of NC's Medicaid system, including perspectives from the state, LME/MCOs, providers, and beneficiaries.…”
Section: Discussionmentioning
confidence: 78%
“…To date, few studies have described provider or patient perspectives regarding the impacts of COVID-19 on OUD treatment. [25][26][27][28][29] The present study expands prior work in other states by adding findings from within a sample of NC's Medicaid system, including perspectives from the state, LME/MCOs, providers, and beneficiaries. Consistent with several prior studies [25][26][27][28] and in contrast to another, 29 these changes were generally well received by providers and patients in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Sixteen in‐depth semi‐structured interviews with a purposeful sample of PPP staff across departments were conducted by our team, which has significant qualitative research experience (Bass et al, 2011 , 2015 ; Gordon et al, 2021 ; Kang et al, 2021 ; Martin et al, 2021 ). Semi‐structured interviews guided conversation and allowed the flexibility to hone discussion towards staff members' roles, experiences and perceptions (Saks & Allsop, 2021 ).…”
Section: Methodsmentioning
confidence: 99%